Creating a Pindh: Place-Making within a Sikh Diasporic Community in Malaya. (2nd January 2016) - Kaur, Narveen
Abstract : This paper examines a diaspora group's claiming and contesting of physical space and actively engaging in host country multiracial spaces, I co-opted the Pindh, a Sikh concept incorporating relationships with the landscape and social structure, re-defining its original meaning to encompass this unique consolidation of identity, home and belonging. Addressing the use and meaning of space and the transformation of Peraktown, the geographical location, I explore this transformation to a place of meaning through the practices of everyday life within the Sikh community. It describes the concepts of spatial relationships and their impact on the construction and solidification of the Peraktown Sikh community in contrast to their inherited connection to the land and inherent romantic nostalgia for Punjab, as they recreated the meanings it contained and inscribed these on the physical map of the town. In the four spaces addressed, the home, the Gurdwara, the school and the gendered work spaces, I demonstrate the ways that space altered, through claiming, adoption and subversion. The lens of the Pindh offers a uniquely Sikh way to view and analyse the constitution of common identity and a place to belong. The Peraktown Sikhs extend the discourse of diaspora beyond postcolonial and Western modes of thought of being 'other' yet simultaneously belonging 'here', 'back there' and to multiple places of home.